Respuesta :
Answer:
x = -3
Step-by-step explanation:
-3(x+3)+9=9
Subtract 9 from each side
-3(x+3)+9-9=9-9
-3(x+3)=0
Divide each side by -3
-3/-3(x+3)=0/-3
x+3 = 0
Subtract 3 from each side
x+3-3 = 0-3
x = -3
Answer: x =-3
Step-by-step explanation: In this equation, our first task is to simplify the left side. So we start by distributing the -3 through both term inside the parentheses.
-3 times x is -3x and -3 times 3 is -9.
So we have -3x - 9 + 9 = 9.
You can simplify the left side one step further by combining
-9 + 9 to get 0.
If you wanted to, you can put a 0 but since it has no value, 0 just cancels out which means that the -9 and +9 disappear
and we have -3x = 9.
Now divide both sides by -3 to isolate x and we get x = -3.